Hemodynamic and cardiorespiratory predictors of sport rock climbing performance - Fryer, S. M.; Giles, D.; Garrido Palomino, I.; de la O Puerta, A.; Espana-Romero, V. (The Journal of Strength and Conditioning Research, 2018)
Rock climbing performance has been suggested to involve a notable contribution from aerobic metabolism. Previously, it has been shown that forearm oxygenation kinetics can be used to distinguish ability groups and predict red-point sport climbing performance. Currently, it is not known if forearm oxygenation kinetics or a sport-specific assessment of cardiorespiratory fitness best predicts sport rock climbing performance. The aim of the study was to determine whether forearm oxidative capacity index, maximal deoxygenation (d score) during a treadwall VO2peak test, treadwall VO2peak, or running VO2max best predicts self-reported sport climbing performance. Twenty-one male sport rock climbers completed a treadwall VO2peak, running VO2max, and an assessment of near-infrared spectroscopy-derived oxidative capacity index. Linear regression, adjusted for age and experience (years), revealed that forearm oxidative capacity index, treadwall maximal deoxygenation (d), and treadwall VO2peak all significantly predicted self-reported red-point sport climbing ability (Adj R 2 = -0.398, -0.255, and 0.374, respectively), whereas treadmill running VO2max did not (Adj R 2 = -0.052). Additionally, multiple regression suggested that the combined significant aerobic predictors accounted for 67% of the variance in red-point climbing ability. Findings suggest that training for sport rock climbing performance should look to incorporate modalities that focus on (a) improving local forearm aerobic capacity and (b) improving whole-body aerobic capacity using sport-specific apparatus, such as treadwalls.